Changes in donor antibody titer levels over time in a military group O low‐titer whole blood program. (13th April 2019) - Bailey, Jonathan D.; Fisher, Andrew D.; Yazer, Mark H.; Howard, Jeffrey T.; Corley, Jason B.; Miles, Ethan A.; Cap, Andrew P.
Abstract : BACKGROUND: The ability to rapidly administer whole blood (WB) at the point of injury is an important intervention to save lives. This can be accomplished using low titer group O WB donors. Titers of immunoglobulin M anti‐A and anti‐B might change over time. This study describes titer testing in a large series of donors. STUDY DESIGN AND METHODS: Data were collected retrospectively from the Armed Services Blood Program and the Theater Medical Data Store. Soldiers assigned to the 75th Ranger Regiment were screened and titered upon completion of training or before deployment or during periodic unit readiness activities. A Ranger group O low‐titer (ROLO) donor was defined as having titers of both anti‐A and ‐B of less than 256 by immediate spin testing. RESULTS: Between May 2015 and January 2017, of a total of 2237 participating soldiers, 1892 (84.5%) soldiers underwent antibody titering once, while 266 (11.9%) were titered twice, 62 (2.8%) were titered three times, and 17 (0.8%) were titered at least four times. The mean age was 26.5 ± 6.5, and 2197 (98.2%) were male. A total of 69.5% of donors met ROLO donor criteria on the first test. The percentage of donors meeting universal‐donor criteria increased to 83.5% on the second test, 91.1% on the third test, and 100% on the fourth and fifth tests. CONCLUSIONS: With successive titer testing, it appears that individuals display a tendency toward lower titers. This may indicate that titer testing may not be required after the second test if donors have been identified initially as low titer.